The Ethnomathematics in a Rural Community of the South of Minas Gerais (Research, Society and Development, 2018)
This article aims to reveal and present analyzes of some non-formal measures and mathematical language games practiced in a community in the south of Minas Gerais, to meet survival needs. In order to achieve this goal, Oral History was used as a qualitative research methodology supported by Ethnomathematics, which considers the processes, techniques and mathematical practices developed in different cultural contexts. Interviews were carried out with residents and among the results obtained, a significant number of non-formal measures that contributed to the construction of the cultural identity of the group studied were highlighted. Based on the two approaches used in this research, the daily use of non-formal measures was designed to reach, through voices from the past, how these measures contributed to the being / know-how of this community, promoting reflection on the policy of dominant knowledge practiced in school, which subtly hides and marginalizes certain contents, knowledge, in the school curriculum.